2007
DOI: 10.1016/j.molmed.2007.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The HER family and cancer: emerging molecular mechanisms and therapeutic targets

Abstract: The human epidermal growth factor receptor (HER) family of transmembrane tyrosine kinases regulate diverse cellular functions in response to extracellular ligands. The deregulation of HER signaling through gene amplification or mutation is seen in many human tumors and an abundance of experimental evidence supports the etiologic role of these events in cancer pathogenesis. In addition, the fact that they are feasible targets for both antibody and small molecule therapeutics has made them highly pursued targets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
106
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 76 publications
0
106
0
3
Order By: Relevance
“…However, the finding of activating mutations in these genes is more recent (reviewed in ref. 71). Functional studies by Wang et al have shown that the HER2 YVMA mutant protein has higher transforming ability than the wild-type HER2 (72).…”
Section: Discussionmentioning
confidence: 99%
“…However, the finding of activating mutations in these genes is more recent (reviewed in ref. 71). Functional studies by Wang et al have shown that the HER2 YVMA mutant protein has higher transforming ability than the wild-type HER2 (72).…”
Section: Discussionmentioning
confidence: 99%
“…After transformation of E. coli XL1-Blue, the proteins were overexpressed, purified via their N-terminal MRGSH 6 tag with nickel-nitrilotriacetic acid superflow resin (Qiagen, Hilden, Germany), and subsequently dialyzed against PBS (pH 7.2) (34).…”
Section: Methodsmentioning
confidence: 99%
“…The rationale for choosing EGFR as a target in cancer therapy was based on the observation that EGFR is overexpressed on the surface of many human cancers, including colorectal cancer, non-small cell cancer of the lung, and gliomas (12). This overexpression is correlated with increased resistance to chemotherapy, more aggressive disease, and poor prognosis (6,13). Moreover, increased receptor expression is often correlated with increased ligand produc- Tables SI-SIII, and an additional reference.…”
Section: The Egf Receptor (Egfr) Has Been Implicated In the Developmentioning
confidence: 99%
“…235 There are compelling new results showing that ERBB3 upregulated activity is a means of escape from therapeutic suppression by several tyrosine kinase inhibitors, in at least six mammary cancer cell lines, by a novel pathway involving feedback from AKT. 127,236 ERBB3 is likely to become increasingly a center of attention for breast cancer treatment.…”
Section: Erbb3 In Normal and Neoplastic Tissues Cell Transformation Bmentioning
confidence: 99%